2013
DOI: 10.1371/journal.pone.0070293
|View full text |Cite
|
Sign up to set email alerts
|

Task and Spatial Frequency Modulations of Object Processing: An EEG Study

Abstract: Visual object processing may follow a coarse-to-fine sequence imposed by fast processing of low spatial frequencies (LSF) and slow processing of high spatial frequencies (HSF). Objects can be categorized at varying levels of specificity: the superordinate (e.g. animal), the basic (e.g. dog), or the subordinate (e.g. Border Collie). We tested whether superordinate and more specific categorization depend on different spatial frequency ranges, and whether any such dependencies might be revealed by or influence si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 60 publications
6
21
0
8
Order By: Relevance
“…Previous studies have also reported greater neural activity for Low than High spatial frequency images at approximately 160ms 31,34,36 . Moreover, similar findings have been reported for overall greater amplitude for High compared with Low spatial frequency faces 35,37,38 , with some studies reporting an earlier modulation than presented here (i.e. the M100 compared with the M170) 37,38 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have also reported greater neural activity for Low than High spatial frequency images at approximately 160ms 31,34,36 . Moreover, similar findings have been reported for overall greater amplitude for High compared with Low spatial frequency faces 35,37,38 , with some studies reporting an earlier modulation than presented here (i.e. the M100 compared with the M170) 37,38 .…”
Section: Resultssupporting
confidence: 91%
“…Moreover, similar findings have been reported for overall greater amplitude for High compared with Low spatial frequency faces 35,37,38 , with some studies reporting an earlier modulation than presented here (i.e. the M100 compared with the M170) 37,38 . This discrepancy may be due to differences in analysis technique, such that statistics on specific electrodes and time-windows are more specific (but also biased) compared with our more conservative and unbiased spatiotemporal analysis, where corrections for multiple comparisons are made across the entire sensor space and all time-points.…”
Section: Resultssupporting
confidence: 91%
“…Thus, we found distinct early (160 ms) and late (460 ms) components of LSF processing despite overwhelmingly greater activity for HSF overall (170 -585 ms). Some studies have reported earlier effects of LSF (i.e., within the M100 component) than our relatively later effect (Craddock et al, 2013;Mu and Li, 2013). This may be due to differences in analysis technique, such that statistics on specific electrodes and time windows are more specific (but also more biased) compared with our more conservative and unbiased spatiotemporal analysis, where corrections for multiple comparisons are made across the entire sensor space and all time-points.…”
Section: Spatiotemporal Analysis Of Meg Sensor Datamentioning
confidence: 43%
“…In particular, the P1 component (a positive peak arising between 80 and 140 ms) is evoked both by LSF and HSF stimuli, and can be either enhanced or reduced to HSF (relative to LSF) stimuli, depending on several factors, including contrast, structural complexity and possibly also task requirements (Baseler & Sutter, 1997;Boeschoten, Kemner, Kenemans, & Engeland, 2005;Craddock, Martinovic, & Müller, 2013;Ellemberg, Hammarrenger, Lepore, Roy, & Guillemot, 2001;Hansen, Jacques, Johnson, & Ellemberg, 2011;Rokszin, Győri-Dani, Nyúl, & Csifcsák, 2016). Similarly, the subsequent N1 component (with a negative peak between 140-220 ms) reflects the cortical analysis of both LSF and HSF images, but its amplitude is modulated by the spectral content of stimuli in an inconsistent way, an effect that is probably paradigm-specific (Boeschoten et al, 2005;Craddock et al 2013;Rokszin et al, 2016). Since the posterior P1 and N1 components reflect continuously unfolding, temporally overlapping processes of visual analysis such as feature detection, figure-ground segregation and structural encoding, and as outlined above, they are both influenced by SFs, these ERPs provide a unique measure for tracking the time course of SF processing in various groups of participants.…”
Section: Introductionmentioning
confidence: 99%